2017
DOI: 10.1016/j.ydbio.2017.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Loss and gain of cone types in vertebrate ciliary photoreceptor evolution

Abstract: Ciliary photoreceptors are a diverse cell type family that comprises the rods and cones of the retina and other related cell types such as pineal photoreceptors. Ciliary photoreceptor evolution has been dynamic during vertebrate evolution with numerous gains and losses of opsin and phototransduction genes, and changes in their expression. For example, early mammals lost all but two cone opsins, indicating loss of cone receptor types in response to nocturnal lifestyle. Our review focuses on the comparison of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 113 publications
0
28
0
Order By: Relevance
“…More recently, this possibility was further supported by a dataset from single cell transcriptomes of mouse retinal cells generated by Macosko et al (36). Reanalysis of this dataset revealed that none of the "pure" Sws1 cones expressed Tbx2, yet some of the cones co-expressing Sws1 and Lws did show Tbx2 expression (28,36). This pattern raises the possibility that the role of Tbx2a in promoting LWS expression could be conserved in even distantly related vertebrate lineages.…”
Section: Tbx2a Is a Major Regulatory Component Of Switching Between Rmentioning
confidence: 94%
See 3 more Smart Citations
“…More recently, this possibility was further supported by a dataset from single cell transcriptomes of mouse retinal cells generated by Macosko et al (36). Reanalysis of this dataset revealed that none of the "pure" Sws1 cones expressed Tbx2, yet some of the cones co-expressing Sws1 and Lws did show Tbx2 expression (28,36). This pattern raises the possibility that the role of Tbx2a in promoting LWS expression could be conserved in even distantly related vertebrate lineages.…”
Section: Tbx2a Is a Major Regulatory Component Of Switching Between Rmentioning
confidence: 94%
“…6). In this region we also identified predicted binding sites for six transcription factors that are known to play key roles in retinal development across vertebrates (28,29); Rxrg, Thrb, Sall3, Vsx1, Rax, and Vsx2 ( Fig. 6).…”
Section: How Has Tbx2a Driven Differences Across Species?mentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative analyses have demonstrated considerable similarity among the ciliary photoreceptors and eyes within vertebrates [12,13]. At the morphological level, vertebrate eyes have a distinct position in respect to the brain, anterior and on the left and right side, and include rod and cone ciliary photoreceptors as well as neurons, pigment cells and other cell types.…”
Section: Introductionmentioning
confidence: 99%